Assessing the Impacts of a Helping Hand: Findings of the Project Understanding Food Pantry Clients' Survey - Cabral, Christina; Gallegos, Brenda; Gross, Ciara; Downey, Dennis (CBR@CSUCI: An annual volume of community-based research, 2019)
This research study was conducted by students in the Sociology Program at CSU Channel Islands as a service-learning project for the senior capstone course. Research consists of 34 qualitative interviews conducted in a one month period at Project Understanding (in both English and Spanish). Findings address the following areas: demographics of clients; patterns of public assistance; circumstances leading to pantry use; sharing of food with community members; components of respondents’ food supply; preferences regarding supplies at pantry; and impacts of the pantry on clients and the community.